Let Us Talk About Human Donation - DS Bhullar; Preetinder Singh Chahal; Gurvinder Singh Kakkar (GMC Patiala Journal of Research and Medical Education, 2019)
Human donation pertains to body donation after death, living or deceased organ, tissues and blood donation. Body donation is gifting dead body for medical education and research covered under the Anatomy Act 1949. Organ and tissue donation is meant for therapeutic purpose only and gives an opportunity to save lives after death or improve quality of life of recipients and is permitted by law under the “Transplantation of Human Organs & Tissues Act 1994” which regulates removal, storage and transplantation of human organs for therapeutic purpose. National Organ and Tissue Transplant Organization (NOTTO) is a national body under Government of India with a vision of saving human lives by preventing premature deaths due to organ failure. It further has its regional (ROTTO) as well as state (SOTTO) networks. As per the ROTTO PGIMER Chandigarh data, Punjab state has topped in donation of cadavers to PGI Chandigarh in five years and the main reasons for these donations are increased awareness within the community, acceptance of the idea of donating combined with efforts of transplant coordinators. Medical fraternity should make organ donation the mass movement becoming organ donors, motivating people at workplace, in community, at place of worship and in civic organizations